PENGARUH DOSIS PUPUK UREA DAN MACAM VARIETAS TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG (Zea mays L.) - Hamidah, Emmy (Universitas Islam Darul Ulum, 2009)
The purpose of this study is to determine the effect of varieties and fertilizer urea on growth and yield of corn. Alleged that the administration of urea fertilizer dose of 300 kg / ha and the use of 16 varieties of ambition will give good results on the growth and production of maize (Zea mays L.). The research concluded that there is interaction between the application of urea and maize varieties in plant height variable age of 14 dap, 28 dap, 42 dap and 56 dap, 28 dap old stem diameter, klobot cob diameter age was 105 dap; diameter peeling old cob 105 dap; cob weight was 105 dap klobot age; peeling cob weight all at the age of 105 days after the treatment of urea 300 kg / ha with 16 varieties ambitions (U2V4). Best research results in the combined treatment of urea fertilizer 300 kg / ha with 16 varieties ambitions.